How different strengths of ties impact project performance in megaprojects: the mediating role of trust. Issue 4 (11th April 2020) - Wu, Guangdong; Li, Huiwen; Wu, Chunlin; Hu, Zhibin
Abstract : Purpose: This study aims to investigate the relationships between the different strengths of ties (strong ties and weak ties), types of trust and project performance in megaprojects. Design/methodology/approach: A questionnaire survey was conducted with various experts and professionals involved in megaprojects, and 350 valid responses were received. Data was analyzed by means of structural equation modeling. Findings: The results show that both strong ties and weak ties have positive impacts on trust in megaprojects, but weak ties have a more significant positive effect than do strong ties. Unexpectedly, the introduction of interorganizational trust significantly weakens the effect of the strength of ties on project performance. The indirect influence of the strength of ties on performance has different paths. Weak ties have an indirect effect via calculative trust and relational trust. However, in a strong ties network, inferior stakeholders lack the information necessary to complete a megaproject, and they believe that calculative trust will not promote project performance until the megaproject is successfully delivered. Thus, the effect of calculative trust on project performance is not significant. Research limitations/implications: These findings provide evidence in regard to strength of ties governance being a part of the effective strategy in improving megaprojects' performance. It also demonstrates the mediating function of trust and advances the current understandings of the underlying mechanism of the strength of ties on project performance, thus providing implications for researchers and practitioners. However, this study has some limitations. For example, the strength of ties and trust between organizations are a dynamic process in megaprojects. This study does not conduct in-depth analysis of the evolution mechanism and investigate the different levels of trust at different stages of the megaproject. Future research can be guided by these directions. Originality/value: The main contribution of this study is fourfold. First, this study enriches the literature on strength of ties by accentuating the roles of trust in megaproject context. Second, this study contributes to the theoretical development of a conceptual model for explaining the interrelationships among strength of ties, types of trust and project performance. Third, this study responds to the call "which dimension (i.e. strong ties or weak ties) is more influential" by exploring the direct and indirect effects of strength of ties on project performance. Finally, this study breaks through the limitation of traditional cognition that megaproject management can be met by relying on rigid contracts. In other words, trust can supplement the weakness of rigid contract by forming contract flexibility with different strength of ties. Meanwhile, the specific strategies to establish and maintain trust are given, such as building information model (BIM) collaboration platform and reputation management mechanism.